Life in Veszprém, in the ”town of queens” - Tibor Lenner (Journal for Geography, 2012)
Every settlement is a unique place. This uniqueness is manifested, among others, in cultural and historical values. Truly reflecting the settlement’s history and development, the ground plan of a town safeguards these unique characteristics over the centuries. Therefore, it is practical to analyse the spatial extension within its historical relations when researching a settlement’s morphology, development and functional structure. This method has traditions dating back to Tibor Mendöl in the Hungarian settlement geography. By means of historical settlement geography, one can interpret the creation of a settlement space, the principles of spatial arrangement, and explore the expansion or regression of a settlement. In the present study, we attempted to find a correlation between the historical, functional and formal aspects of the transformation processes on the example of Veszprém, a county capital in Transdanubia. The authors’ aim of doing so was to establish a basis for a later settlement-morphological examination of the town.